2019
DOI: 10.1111/pedi.12828
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of type 2 diabetes among adolescents in Brazil: Findings from Study of Cardiovascular Risk in Adolescents (ERICA)

Abstract: Background Type 2 diabetes mellitus (T2DM) in adolescents represents a clinical challenge related to lifestyle and obesity; however, only a few data are available in developing countries. Therefore, our aim was to investigate the prevalence of T2DM and prediabetes among Brazilian adolescents, as well as to describe the cardio‐metabolic profile according to the diagnosis. Methods This is a cross‐sectional school‐based multicenter study including youth aged 12 to 17 years from cities with more than 100 000 inhab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 39 publications
2
15
1
3
Order By: Relevance
“…One-third of diabetes cases were T2D diabetes in our study, which is consistent with the increasing prevalence of T2D among children observed in some countries in the last decade [2]. The prevalence of T2D in our study was much lower than the prevalence among Brazilian school children aged 12-17 years old in 2013-2014 (3.3%) [23] and slightly lower than the prevalence reported in the USA in 2009 among children aged 10-19 years old (0.046%) [24]. Another school-based study in the Tokyo Metropolitan area of Japan reported the overall incidence of T2D (per 100,000 person-year) during the 1975-2015 period was 0.8 in WTH: waist-to-hip ratio; BMI: body mass index.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…One-third of diabetes cases were T2D diabetes in our study, which is consistent with the increasing prevalence of T2D among children observed in some countries in the last decade [2]. The prevalence of T2D in our study was much lower than the prevalence among Brazilian school children aged 12-17 years old in 2013-2014 (3.3%) [23] and slightly lower than the prevalence reported in the USA in 2009 among children aged 10-19 years old (0.046%) [24]. Another school-based study in the Tokyo Metropolitan area of Japan reported the overall incidence of T2D (per 100,000 person-year) during the 1975-2015 period was 0.8 in WTH: waist-to-hip ratio; BMI: body mass index.…”
Section: Discussionsupporting
confidence: 90%
“…It is challenging to compare and interpret the prevalence of prediabetes in children between countries due to several reasons, such as the difference in the definition used, age groups of the sample populations, or different settings (i.e., whole population vs. obese children). The prevalence of impaired fasting glucose among children found in our study (6.1%) was lower than the prevalence reported in the study in Brazil (22%) [23] though similar to the [27]. However, the prevalence of prediabetes in our study was double the prevalence among children and adolescent in urban South India in 2013 (3.4%) [28] and triple the prevalence reported in a Chinese study among children aged 6-17 (1.89%) [29].…”
contrasting
confidence: 59%
“…National Diabetes Statistik Report tahun 2017 melaporkan bahwa prevalensi Diabetes pada anak-anak dan remaja di Amerika tahun 2015 diperkirakan 7,2% dari total penduduk usia anak dan remaja dengan jumlah 132.000 anak usia kurang dari 18 tahun dan 193.000 anak usia kurang dari 20 tahun (Center of Desease Control and Prevention, 2017). Di Brazil, prevalensi pradiabetes dan Diabetes Melitus tipe 2 masing-masing adalah 22,% dan 3,3% dari populasi penduduk di Brasil dimana sekitar 213.830 remaja hidup dengan DM tipe 2 dan 1,46 juta remaja dengan pradiabetes (Telo et al, 2019). Di Inggris, insiden Diabetes Melitus tipe 2 tahun 2015 dan 2016 pada anak-anak berusia <17 tahun adalah 0,72 per 100.000 per tahun (Candler et al, 2017).…”
Section: Pendahuluanunclassified
“…In Brazil, the prevalence of T2D has increased by 24% between 2006 and 2019 [10] and an estimate of 65,581 deaths have been shown to be caused by diabetes among adults aged 35-80 years [11]. It has been reported that the prevalence of prediabetes and T2D among Brazilian adolescents were 22.0% and 3.3%, respectively [12]. Studies have also demonstrated the occurrence of cardiometabolic risk factors including abdominal obesity, high Maria Aderuza Horst, Karani Santhanakrishnan Vimaleswaran have contributed equally to this work.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also demonstrated the occurrence of cardiometabolic risk factors including abdominal obesity, high Maria Aderuza Horst, Karani Santhanakrishnan Vimaleswaran have contributed equally to this work. insulin levels, dyslipidaemia, and high blood pressure among Brazilian adolescents [12][13][14]. Hence, early interventions targeting these factors might be an effective strategy to prevent or slow the progression of T2D and decrease the risk of CVD and associated premature mortality [8].…”
Section: Introductionmentioning
confidence: 99%